2012
DOI: 10.1371/journal.pone.0036767
|View full text |Cite
|
Sign up to set email alerts
|

Adult-Age Inflammatory Pain Experience Enhances Long-Term Pain Vigilance in Rats

Abstract: BackgroundPrevious animal studies have illustrated a modulatory effect of neonatal pain experience on subsequent pain-related behaviors. However, the relationship between chronic pain status in adulthood and future pain perception remains unclear.Methodology/Principal FindingsIn the current study, we investigated the effects of inflammatory pain experience on subsequent formalin-evoked pain behaviors and fear conditioning induced by noxious stimulation in adult rats. Our results demonstrated an increase of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 73 publications
(85 reference statements)
2
7
0
Order By: Relevance
“…Rats injected with CFA exhibited pronounced thermal hyperalgesia that developed within 1 day and persisted through 14 days following injection. This observation is similar to that of previous reports on the temporal profile of thermal hyperalgesia in CFA-induced chronic pain model (Wang et al, 2009 ; Li et al, 2012 ). Three-way ANOVA revealed that PWLs were significantly modulated by “group” ( F (1,19) = 5.8, p = 0.03), “time” ( F (5,95) = 7.5, p < 0.0001), “stimulation site” ( F (1,19) = 43.8, p < 0.0001), interactions between two factors (“group” × “stimulation site”: F (1,19) = 41.0, p < 0.0001 ; “time” × “stimulation site”: F (5,95) = 9.5, p < 0.0001; “group” × “time”: marginal significance, F (5,95) = 2.2, p = 0.06), and the interaction between three factors ( F (5,95) = 7.6, p < 0.0001).…”
Section: Resultssupporting
confidence: 93%
“…Rats injected with CFA exhibited pronounced thermal hyperalgesia that developed within 1 day and persisted through 14 days following injection. This observation is similar to that of previous reports on the temporal profile of thermal hyperalgesia in CFA-induced chronic pain model (Wang et al, 2009 ; Li et al, 2012 ). Three-way ANOVA revealed that PWLs were significantly modulated by “group” ( F (1,19) = 5.8, p = 0.03), “time” ( F (5,95) = 7.5, p < 0.0001), “stimulation site” ( F (1,19) = 43.8, p < 0.0001), interactions between two factors (“group” × “stimulation site”: F (1,19) = 41.0, p < 0.0001 ; “time” × “stimulation site”: F (5,95) = 9.5, p < 0.0001; “group” × “time”: marginal significance, F (5,95) = 2.2, p = 0.06), and the interaction between three factors ( F (5,95) = 7.6, p < 0.0001).…”
Section: Resultssupporting
confidence: 93%
“…We further showed that this carrageenan‐induced inflammatory pain memory facilitated the occlusal interference‐induced masseter muscle hyperalgesia. Our results were consistent with previous studies, which showed that the later perception of pain is associated with the previous inflammatory stimulation in a model of repeated inflammatory pain in the hind paws (Kayser et al., ; Li et al., ). Our results were also in good agreement with results of the clinical trials, which showed that children who displayed great distress at lumbar punctures experienced aggravated distress during subsequent lumbar punctures (Chen et al., ); their direct experience of pain intensity and their adult behaviour during venipuncture were related to their memories of past procedures (Noel et al., ).…”
Section: Discussionsupporting
confidence: 94%
“…A custom-designed Plexiglas chamber (22 × 22 × 30 cm) was used (Li et al, 2012 ). The chamber had holes (3-mm diameter at 3-mm intervals) in the bottom and a speaker on its back wall.…”
Section: Methodsmentioning
confidence: 99%
“…Stimulus-elicited behaviors (Fan et al, 1995 ; Li et al, 2012 ) were scored as follows: 0, immobility; 1, head turning (shaking or elevating the head); 2, flinching (a small abrupt jerking body movement); 3, withdrawal (retracted of the paw away from the stimulus) or licking (paw retraction flowed by licking of that paw); and 4, body movement (body turning and running). The rats were videotaped throughout the experiment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation